LANGUAGE CHOICE ON UNIVERSITY WEBSITES IN ARAB COUNTRIES - Callahan, Ewa; Kirshenbaum, Nurit (AoIR Selected Papers of Internet Research, 2015)
With the Internet unremittingly crossing boundaries, allowing more efficient communication and cooperation among people in different countries and cultures, the issue of common language is often brought into discussion. Currently English is considered the international lingua franca, but this mode of communication also allows other languages to have a strong presence on the web. The major study in this area was research conducted by Callahan and Herring (2012). This longitudinal study examined changes in language choices in 1140 universities in 57 countries over the period of 5 years. The study proposed a tri-level multiglossia model, where national language is the core language, English, as the lingua franca, the first additional language, and other smaller languages aiming at particular groups of potential customers or collaborators. This research attempts to follow up on the study by Callahan and Herring and explore the linguistic mosaic of university websites in Arab countries, attempting to answer questions about the level of multilingualism and the choice of primary and secondary languages, as well as how well the Arab countries follow the tri-level multiglossia model.